How to Analyse Comprehension in Print Advertising: Advertising Effect from a Peircean Perspective - Andersen, Christian; Sørensen, Bent (Signs - International Journal of Semiotics, 2009)
The present article shows how the composition of an advertisement influences the creation of comprehension in the receiving process. It is suggested that composition is a varying structure of inference fields, and on this foundation, it is emphasised how composition is underrated in consumer research and in its classical modelling of the cognitive effect of advertising, especially comprehension as an effect, and as a contributing factor in the ongoing mental assimilation of the message in general. That composition is an important factor in an advertisement’s cognitive construction of the message is demonstrated via a so-called reduction analysis, that is, an operation in the ad’s composition; its inference fields. This reduction analysis is meant as a preliminary method to establish hypotheses concerning how the composition supports different kinds of comprehension, and to be able to further test such hypotheses experimentally.